Using the Transcription Factor Inhibitor of DNA Binding 1 to Selectively Target Endothelial Progenitor Cells Offers Novel Strategies to Inhibit Tumor Angiogenesis and Growth - Mellick, Albert S. (2010)
Tumor angiogenesis is essential for malignant growth and metastasis. Bone marrow (BM)-derived endothelial progenitor cells (EPCs) contribute to angiogenesis-mediated tumor growth. EPC ablation can reduce tumor growth, however, the lack of a marker that can track EPCs from the BM to tumor neovasculature has impeded progress in understanding the molecular mechanisms underlying EPC biology. Here, we report the use of transgenic mouse and lentiviral models to monitor the BM-derived compartment of the tumor stroma; this approach exploits the selectivity of the transcription factor inhibitor of DNA binding 1(Id1) for EPCs to track EPCs in the BM, blood, and tumor stroma, as well as mature EPCs. Acute ablation of BM-derived EPCs using Id1-directed delivery of a suicide gene reduced circulating EPCs and yielded significant defects in angiogenesis-mediated tumor growth. Additionally, use of the Id1 proximal promoter to express miR-30 based short hairpin RNA inhibited expression of critical intrinsic EPC factors, confirming that signaling through VEGFR2 is required for EPC mediated tumor biology. By exploiting the selectivity of Id1 gene expression in EPCs, our results establish a strategy to track and target EPCs in vivo, clarifying the significant role that EPCs play in BM-mediated tumor angiogenesis.